ПАРЛАМЕНТЫН ЗАСАГЛАЛТАЙ ОРНУУДЫН ЗАСГИЙН ГАЗРЫН БҮРДЭЛТ - Б.Одгэрэл (Politology, 2023)
This paper is preliminary comparative analysis of cabinet composition and coalition types of issues in the world. Coalition is one of the cabinet types, so we can classify them like this: Great coalition, minimal wining coalition, minoritary coalition. As a country of Parliamentary power, Mongolia has created its government in accordance with the principle to create the Cabinet during the parliamentary power. There were existed two types of cabinets: Majority cabinet and coalition cabinet. Author proposed by this article is to review theory of coalition and comparative methodology used by contemporary western.